Leadership and Conceptions of Organization: Contours of the Distributed Perspective (LEARNing Landscapes, 2008)
This paper discusses the theoretical bases of various leadership perspectives and focuses in on one of them: distributed leadership. The learning organization conception of the sociology of organizations is proposed as the theoretical support of distributed leadership. Although a growing number of research findings point to the effectiveness of this perspective on school outcomes, there is need for further research in this area. To be successfully enacted, distributed leadership should be exerted in an organization which truly espouses the principles of a learning organization.
Keywords: leadership; distributed leadership; school outcome; educational organization